BULK-ROCK MAJOR AND TRACE ELEMENT COMPOSITIONS OF ABYSSAL PERIDOTITES: IMPLICATIONS FOR MANTLE MELTING, MELT EXTRACTION AND POST-MELTING PROCESSES BENEATH MID-OCEAN RIDGES - Niu Y. (My University, 2004)
This paper presents the first comprehensive major and trace element data for $130 abyssal peridotite samples from the Pacific and Indian ocean ridge–transform systems. The data reveal important features about the petrogenesis of these rocks, mantle melting and melt extraction processes beneath ocean ridges, and elemental behaviours. Although abyssal peridotites are serpentinized, and have also experienced seafloor weathering, magmatic signatures remain well preserved in the bulk-rock compositions. The better inverse correlation of MgO with progressively heavier rare earth elements (REE) reflects varying amounts of melt depletion. This melt depletion may result from recent sub-ridge mantle melting, but could also be inherited from previous melt extraction events from the fertile mantle source. Light REE (LREE) in bulk-rock samples are more enriched, not more depleted, than in the constituent clinopyr-oxenes (cpx) of the same sample suites. If the cpx LREE record sub-ridge mantle melting processes, then the bulk-rock LREE must reflect post-melting refertilization. The significant correlations of LREE (e.g. La, Ce, Pr, Nd) with immobile high field strength elements (HFSE, e.g. Nb and Zr) suggest that enrichments of both LREE and HFSE resulted from a common magmatic process. The refertilization takes place in the 'cold' thermal boundary layer (TBL) beneath ridges through which the ascending melts migrate and interact with the advanced residues. The refertilization appar-ently did not affect the cpx relics analyzed for trace elements. This observation suggests grain-boundary porous melt migration in the TBL. The ascending melts may not be thermally 'reactive', and thus may have affected only cpx rims, which, together with pre-cipitated olivine, entrapped melt, and the rest of the rock, were subsequently serpentinized. Very large variations in bulk-rock Zr/Hf and Nb/Ta ratios are observed, which are unexpected. The correlation between the two ratios is consistent with observa-tions on basalts that D Zr /D Hf < 1 and D Nb /D Ta < 1. Given the identical charges (5 þ for Nb and Ta; 4 þ for Zr and Hf) and essentially the same ionic radii (R Nb /R Ta ¼ 1Á000 and R Zr / R Hf ¼ 1Á006–1Á026), yet a factor of $2 mass differences (M Zr /M Hf ¼ 0Á511 and M Nb /M Ta ¼ 0Á513), it is hypothe-sized that mass-dependent D values, or diffusion or mass-transfer rates may be important in causing elemental fractionations during porous melt migration in the TBL. It is also possible that some 'exotic' phases with highly fractionated Zr/Hf and Nb/Ta ratios may exist in these rocks, thus having 'nugget' effects on the bulk-rock analyses. All these hypotheses need testing by constraining the storage and distribution of all the incompatible trace elements in mantle peridotite. As serpentine contains up to 13 wt % H 2 O, and is stable up to 7 GPa before it is transformed to dense hydrous magnesium silicate phases that are stable at pressures of $5– 50 GPa, it is possible that the serpentinized peridotites may survive, at least partly, subduction-zone dehydration, and transport large amounts of H 2 O (also Ba, Rb, Cs, K, U, Sr, Pb, etc. with elevated U/Pb ratios) into the deep mantle. The latter may contribute to the HIMU component in the source regions of some oceanic basalts. KEY WORDS: abyssal peridotites; serpentinization; seafloor weathering; bulk-rock major and trace element compositions; mantle melting; melt extraction; melt–residue interaction; porous flows; Nb/Ta and Zr/Hf fractionations; HIMU mantle sources
Keywords: abyssal peridotites; serpentinization; seafloor weathering; bulk-rock major and trace element compositions; mantle melting; melt extraction; melt–residue interaction; porous flows; Nb/Ta and Zr/Hf fractionations; HIMU mantle sources